Role of brain natriuretic peptide in the pathogenesis of resistant hypertension - K. Yu. Nikolaev; A. V. Shilova; A. Ya. Kovaleva; G. I. Lifshits (Российский кардиологический журнал)
Modern medicine has successfully used the N-terminal pro-brain natriuretic peptide (NT-proBNP) as a biomarker for many cardiovascular diseases (CVDs). According to a number of studies, NT-proBNP may also play a role in the development of resistant hypertension (RH), but the existing work addresses this issue only indirectly. In turn, RH causes serious damage to the economic and social spheres, worsening the quality of life of patients. Thus, the complexity of verification and treatment of RH, the inconsistency of the described associations of NT-proBNP and RH makes this topic more relevant than ever.